Membangun Kemandirian Ekonomi Desa melalui Peningkatan Daya Saing Potensi Kekayaan Alam Perdesaan - Lina Krisnawati; Adi Susanto; Sutarmin Sutarmin (Universitas Proklamasi 45 Yogyakarta, 2019)
As many as 83% of Indonesia's territory is rural. Each region has natural resource potential. However, it is still rarely managed properly. If managed properly, it has the potential to create economic independence from each of these villages. Currently, Indonesia has a total of 70,611 villages. Of the total villages, 49.9% or 32,379 of them are underdeveloped villages. In Central Java, currently there are 40.5% of disadvantaged villages or 3,467 villages out of 8,564 villages. Village empowerment provides great benefits for the welfare of the lives of rural communities. The concept of OVOP (one village one product) is one of the concepts or models of village self- sufficiency. Research is needed to explore the potential of a village and how its development planning strategy. In the process of development, villages are empowered to be economically independent and their people's welfare will increase significantly. The study aims to identify resources, strength, weakness, opportunity, and threat factors, analyze the position of competitiveness, and formulate strategies to realize the Sunyalangu as an economically self-sufficient village. Data collection methods in this study used Secondary Data Review (SDR), Direct Observation, Semi-Structured Interview (SSI), and Focus Group Discussion (FGD), while the sample of the informants in this study were determined purposively by certain criteria or guidelines.